Asymmetric coating diaphragm based on compounding of porous material and ceramic material

By using asymmetric coating technology that combines porous materials and ceramic materials on the battery separator, the existing separator is easily shrinkable and insufficient electrochemical performance at high temperatures, and the high energy density, excellent rate-performance of the battery is achieved. Cycle stability and improved usage safety.

CN119447707APending Publication Date: 2025-02-14ZJU HANGZHOU GLOBAL SCI & TECH INNOVATION CENT

Patent Information

Application Number
CN202510018382.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing battery separators are prone to shrink at high temperatures and are easily punctured by dendrites, causing short circuits inside the battery, which in turn causes safety accidents such as combustion and explosion; at the same time, the increase in the overall thickness of the coated separators will lead to an increase in impedance and reduce the charging of the battery. Discharge efficiency, rateability and cycle stability are also affected.

Method used

Asymmetrically coated diaphragm based on the composite of porous materials and ceramic materials, by combining porous materials and ceramic materials on both sides of the base film, the porous materials can be used to improve ionic conductivity and inhibit dendrites' growth; ceramic materials provide heat Stability and mechanical strength improve battery safety.

Benefits of technology

It improves the energy density, rateability and cycle stability of the battery, enhances the safety of the battery, and avoids the overpotential and heat accumulation problems caused by single coating of porous materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447707A_ABST
    Figure CN119447707A_ABST
Patent Text Reader

Abstract

The invention provides a porous material and ceramic material composite asymmetric coating diaphragm, which comprises a base membrane, one side of the base membrane is provided with a porous material coating, and the other side of the base membrane is provided with a ceramic material coating. The porous material and the ceramic material are compounded on the two sides of the base membrane respectively, and the pore channel structure of the porous material is utilized, so that the ionic conductivity is improved, dendritic crystal growth is inhibited, and the energy density of the battery is improved; by virtue of excellent thermal stability and mechanical strength of the ceramic material, a supporting effect is provided for the base membrane, and the use safety of the battery is improved; and meanwhile, the problems of overlarge overpotential caused by structural decomposition and accumulation of heat in the battery caused by small heat conductivity coefficient which are easily accompanied when the porous material is singly coated are avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery separators, and in particular relates to an asymmetric coating separator based on a composite of porous material and ceramic material. Background Art

[0002] At present, the market has put forward higher requirements for battery performance, mainly in terms of higher safety, better rate performance and cycle stability. However, it is difficult for existing separators to meet the above increasingly stringent requirements. For example, traditional polyolefin separators (PE film, PP film, PP / PE / PP film) are easy to shrink at high temperatures and are easily punctured by dendrite products, causing internal short circuits in the battery, which in turn lead to safety accidents such as combustion and explosion.

[0003] Patent applications CN105789539A and CN111509168A disclose coated diaphragms that utilize coating materials such as boehmite and alumina to enhance the diaphragm's resistance to heat shrinkage and improve the battery's safety of use. However, this can also affect the battery's electrochemical performance. For example, the increase in overall thickness of the coated diaphragm causes an increase in impedance, which reduces the battery's charge and discharge efficiency. Binder swelling in the coating blocks the coating's pores, and the coating covers the diaphragm's channels, both of which affect ion conduction and reduce the battery's rate capability and cycle stability.

[0004] Patent applications CN116435709A and CN116345068A disclose coated diaphragms that partially or completely replace ceramic materials with porous materials, which can largely solve the problem of ceramic coatings hindering ion transmission and improve the electrochemical performance of batteries. However, this type of coated diaphragm also faces several problems: 1) In the process of preparing the coating slurry by mixing porous materials and ceramic materials, due to the large differences in the surface and interface properties of the materials, particles will agglomerate during the slurry making process, making it difficult to obtain a slurry with uniform composition, which affects the thermal stability of the coated diaphragm; 2) The thermal conductivity of porous materials is poor, and heat cannot be transferred out quickly, which easily causes heat accumulation, thereby affecting the thermal stability of the battery diaphragm; 3) Some porous materials will decompose under the action of the high-voltage positive electrode, resulting in excessive overpotential of the battery, affecting battery performance. Summary of the invention

[0005] In order to solve the above technical problems existing in the prior art, the present invention provides an asymmetric coated diaphragm based on a composite of porous materials and ceramic materials. By composite porous materials and ceramic materials on both sides of the base membrane, the pore structure of the porous material is used to improve the ion conductivity, inhibit the growth of dendrites, and increase the energy density of the battery; relying on the excellent thermal stability and mechanical strength of the ceramic material, the base membrane is supported to improve the safety of the battery; at the same time, the problem of excessive overpotential caused by structural decomposition and heat accumulation inside the battery caused by low thermal conductivity, which is easy to be accompanied by the single coating of porous materials, is avoided.

[0006] The present invention provides an asymmetric coated diaphragm based on a composite of porous material and ceramic material, comprising a base membrane, one side of the base membrane is provided with a porous material coating, and the other side of the base membrane is provided with a ceramic material coating.

[0007] Preferably, the thickness of the porous material coating is 1-15 μm; the thickness of the ceramic material coating is 1-15 μm.

[0008] Further preferably, the porous material coating has a thickness of 2-10 μm; the ceramic material coating has a thickness of 2-10 μm. Within this coating thickness range, the asymmetric coated diaphragm has good ionic conductivity and thermal shrinkage resistance. Most preferably, the porous material coating has a thickness of 5 μm; the ceramic material coating has a thickness of 5 μm.

[0009] Preferably, the particle size of the porous material is 1-1500 nm; the particle size of the ceramic material is 1-5000 nm.

[0010] Further preferably, the particle size of the porous material is 50-1000 nm; the particle size of the ceramic material is 100-1500 nm.

[0011] More preferably, the particle size of the porous material is 100-500 nm; the particle size of the ceramic material is 150-600 nm.

[0012] The particle size range of the porous material and the particle size range of the ceramic material can both reduce the difficulty of material synthesis and avoid the looseness of the coating due to the large particle size.

[0013] Preferably, the porous material in the porous material coating is selected from one or more of metal organic framework materials, covalent organic framework compound materials, Prussian blue materials and zeolite molecular sieve materials. These porous materials have large porosity and regular pore structure, which are conducive to uniform transmission of ions and inhibit dendrite formation.

[0014] Preferably, the ceramic material in the ceramic material coating is selected from one or more of aluminum oxide, boehmite, silicon oxide, zirconium oxide, titanium oxide, calcium oxide, zinc oxide, aluminum nitride, boron nitride, silicon nitride and silicon carbide. These ceramic materials have high mechanical strength, good thermal stability and flame retardancy, which are conducive to inhibiting thermal shrinkage of the diaphragm and improving the safety of the battery.

[0015] Further preferably, the metal element in the metal organic framework material is selected from one or more of zinc, zirconium, iron, manganese, magnesium, aluminum, calcium, lanthanum and cerium; the organic ligand in the metal organic framework material is selected from one or more of terephthalic acid, isophthalic acid, fumaric acid, 2-methylimidazole, trimesic acid and derivatives of the above organic ligands.

[0016] Preferably, the base film is a composite of one or more of polyolefin films, polydimethylsiloxane films, polyester films, polyamide films, polyimide films, glass fiber films and non-woven fabrics.

[0017] Preferably, both the porous material coating and the ceramic material coating contain a binder; the binder is selected from one or more of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, styrene-butadiene latex, chitosan, polyvinyl alcohol, polyvinyl ethyl ether, polyacrylic acid, polymethyl methacrylate, and guar gum.

[0018] Preferably, the amount of binder added to the porous material coating accounts for 3wt%-70wt% of the total solid mass of the porous material coating, and the amount of binder added to the ceramic material coating accounts for 1wt%-40wt% of the total solid mass of the ceramic material coating.

[0019] Further preferably, the amount of binder added in the porous material coating accounts for 15wt%-50wt% of the total solid mass of the porous material coating, and the amount of binder added in the ceramic material coating accounts for 5wt%-30wt% of the total solid mass of the ceramic material coating.

[0020] More preferably, the amount of binder added to the porous material coating accounts for 10wt%-40wt% of the total solid mass of the porous material coating, and the amount of binder added to the ceramic material coating accounts for 5wt%-15wt% of the total solid mass of the ceramic material coating.

[0021] The range of the proportion of the adhesive added in the porous material coating and the ceramic material coating can ensure that the coating has good adhesion, and can also avoid poor air permeability of the diaphragm due to excessive adhesive, or high viscosity of the slurry that makes it difficult to coat.

[0022] Preferably, the composite material is prepared by any composite method including blade coating, roller coating, spray coating, spin coating, dipping, filter pressing, suction filtration, casting and hot pressing.

[0023] Preferably, the solvent used in the composite method is selected from one or more of water, methanol, ethanol, isopropanol, ethyl acetate, N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylformamide and N,N-dimethylacetamide.

[0024] The present invention also provides a secondary battery, which is a lithium ion battery or a sodium ion battery; the secondary battery comprises a positive electrode sheet, a negative electrode sheet and a separator, the separator uses the above-mentioned asymmetric coated separator, and the side of the separator provided with a porous material coating faces the negative electrode sheet or the positive electrode sheet. Preferably, the side of the separator provided with a porous material coating faces the negative electrode sheet, and the porous material can even out the ion flow and inhibit the formation of dendrites due to its orderly pore structure.

[0025] Compared with the prior art, the present invention has the following beneficial effects: 1) The present invention utilizes the pore structure of the porous material itself in the porous material coating to provide more transmission paths for ions, compensating for the negative effects caused by the reduction of the membrane porosity due to the coating coverage and the blocking of the coating pores due to the swelling of the binder, thereby promoting ion transmission and improving the rate and recyclability of the battery; 2) The asymmetric coated diaphragm based on the composite of porous material and ceramic material provided by the present invention utilizes the regular pore structure of the porous material and the uniform ion flow to inhibit the growth of dendrites; 3) The present invention utilizes a ceramic material coating with excellent mechanical properties and thermal stability to support and strengthen the base membrane structure, thereby improving the overall heat shrinkage resistance of the diaphragm and improving the safety of the battery; 4) The present invention reduces the adverse effects of heat accumulation inside the battery and reduced safety caused by a single coating of porous materials, and can also avoid the drawbacks of blocked ion transmission caused by a single coating of ceramic materials, thus meeting the requirements of a new generation of battery coating diaphragms. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a schematic diagram of the structure of the asymmetric coated diaphragm based on the composite of porous material and ceramic material of the present invention.

[0027] Figure 2 is a SEM image of the asymmetric coated diaphragm in Example 1, wherein Figure 2 (a)-(b) show the porous material ZIF-8 at different magnifications. Figure 2 (c)-(d) show the ceramic material alumina at different magnifications.

[0028] Figure 3 It is the cycle test performance diagram of Example 1 and Comparative Example 2. DETAILED DESCRIPTION

[0029] The following examples further illustrate the content of the present invention, but should not be construed as limiting the present invention. Without departing from the spirit and essence of the present invention, all other contents obtained by making some equivalent improvements and simple modifications to the present invention belong to the scope of the present invention. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art.

[0030] It should be noted that in the process of preparing the asymmetric composite membrane of the present patent application, the porous material, the ceramic material, and the coated membrane need to be dried, and the drying temperature and drying time are not limited until constant weight is reached. Preferably, the drying temperature is 60-150 °C, and the drying time is 1-12 h.

[0031] It should be noted that in the process of preparing the asymmetric composite diaphragm of the present patent application, it is necessary to prepare a coating slurry, and the solid content of the coating slurry is related to many factors such as the coating method, coating equipment, operating parameters, etc. Considering that the present invention is applied to protect an asymmetric coated diaphragm based on a composite of porous materials and ceramic materials, rather than a slurry formula, the solid content range in the slurry is not limited, and the actual coating shall prevail.

[0032] Example 1

[0033] 1) Place 135 g of MOF material ZIF-8 (CAS: 59061-53-9) in a vacuum oven, set the drying temperature to 120 °C, and the drying time to 12 hours to remove moisture and other impurities adsorbed by the material.

[0034] 2) The dried ZIF-8 in step 1) was mixed with 15 g of polyvinylidene fluoride (PVDF, as a binder), fully ground and added with 850 g of N-methylpyrrolidone (as a solvent), and a uniform slurry was obtained by ultrasonic treatment, wherein the mass of the binder PVDF accounted for 10% of the total mass of the binder and the porous material (ZIF-8).

[0035] 3) The ZIF-8 slurry obtained in step 2) is evenly scraped onto the surface of one side of a commercial 9 μm thick PE diaphragm (as a base film), and placed in a vacuum oven for drying. The drying temperature is set to 80 °C and dried until constant weight (solvent removal). The resulting diaphragm structure is ZIF-8 / PE, in which the ZIF-8 coating thickness is 5 μm.

[0036] 4) Place 285 g of alumina in a vacuum oven, set the drying temperature to 120 °C, and the drying time to 12 hours to remove moisture and other impurities adsorbed by the material.

[0037] 5) The dried alumina (ceramic material) in step 4) is mixed with 15 g of polyvinylidene fluoride (PVDF, as a binder), fully ground and 700 g of N-methylpyrrolidone (as a solvent) is added, and a uniform slurry is obtained by ultrasonic treatment, wherein the mass of the binder PVDF accounts for 5% of the total mass of the binder and the ceramic material.

[0038] 6) The alumina slurry obtained in step 5) is evenly scraped onto the other side of the ZIF-8 / PE composite diaphragm obtained in step 3), and then placed in a vacuum oven for drying. The drying temperature is set to 80 °C and dried until constant weight (solvent removal). The obtained asymmetric coated diaphragm structure is ZIF-8 / PE / Al2O3, wherein the Al2O3 coating thickness is 5 μm.

[0039] Example 2 The ZIF-8 in Example 1 was replaced by UIO-66 (CAS: 1072413-89-8), and the remaining steps were the same to prepare UIO-66 / PE / Al2O3.

[0040] Example 3 The ZIF-8 in Example 1 was replaced by an iron-based Prussian blue analog (Fe-PBA), and the remaining steps were the same to prepare Fe-PBA / PE / Al2O3.

[0041] Example 4 The alumina in Example 1 was replaced by boehmite, and the remaining steps were the same to prepare ZIF-8 / PE / boehmite.

[0042] Example 5 The thickness of the porous material coating in Example 1 was set to 2 μm, the thickness of the ceramic material coating was set to 2 μm, and the remaining steps were the same to obtain ZIF-8 / PE / Al2O3.

[0043] Example 6 The proportion of PVDF added in the porous material coating in the total solid mass of the porous material coating in Example 1 is set to 40wt%, and the proportion of PVDF added in the ceramic material coating in the total solid mass of the ceramic material coating is set to 15wt%. The thickness of the porous material coating is 10 μm, the thickness of the ceramic material coating is 10 μm, and the remaining steps are the same to obtain ZIF-8 / PE / Al2O3.

[0044] Comparative Example 1 The commercial 9 μm PE separator was used directly without any treatment.

[0045] Comparative Example 2 1) Place 570 g of alumina in a vacuum oven, set the drying temperature to 120 °C, and dry for 12 hours to remove moisture and other impurities adsorbed by the material.

[0046] 2) The dried alumina (ceramic material) in step 1) was mixed with 30 g of polyvinylidene fluoride (PVDF, as a binder), fully ground and added with 1400 g of N-methylpyrrolidone (as a solvent), and a uniform slurry was obtained by ultrasonic treatment, wherein the mass of the binder PVDF accounted for 5% of the total mass of the binder and the ceramic material.

[0047] 3) The alumina slurry obtained in step 2) is evenly coated on both sides of a commercial 9 μm thick PE diaphragm (as a base film), and then placed in a vacuum oven for drying. The drying temperature is set to 80 °C and dried until constant weight (the solvent is removed) to obtain a double-sided alumina coated diaphragm Al2O3 / PE / Al2O3, wherein the Al2O3 coating thickness is 5 μm.

[0048] Comparative Example 3 1) Place 270 g of MOF material ZIF-8 (CAS: 59061-53-9) in a vacuum oven, set the drying temperature to 120 °C, and the drying time to 12 hours to remove moisture and other impurities adsorbed by the material.

[0049] 2) The dried ZIF-8 in step 1) was mixed with 30 g of polyvinylidene fluoride (PVDF, as a binder), fully ground and added with 1700 g of N-methylpyrrolidone (as a solvent), and a uniform slurry was obtained by ultrasonic treatment, wherein the mass of the binder PVDF accounted for 10% of the total mass of the binder and the porous material (ZIF-8).

[0050] 3) The ZIF-8 slurry obtained in step 2) was evenly scraped onto both sides of a commercial 9 μm thick PE diaphragm (as a base film), and placed in a vacuum oven for drying. The drying temperature was set to 80 °C and dried until constant weight (the solvent was removed) to obtain a double-sided ZIF-8 coated diaphragm ZIF-8 / PE / ZIF-8, wherein the ZIF-8 coating thickness was 5 μm.

[0051] Test Example 1 Figure 1 Schematic diagram of the structure of the asymmetric coated diaphragm prepared in each embodiment.

[0052] Figure 2 These are electron microscope images of the porous material ZIF-8 and the ceramic material alumina used in Example 1 at different magnifications.

[0053] Depend on Figure 2 From (a) in the figure, we can see that the particle size distribution of ZIF-8 is between 100-500 nm. It should be noted that during the preparation process, porous materials will aggregate to form secondary particles (such as Figure 2In (b)), the particle size of the secondary particles is large and the distribution range is wider, ranging from tens of nanometers to several microns. In the subsequent preparation of the coating slurry, after mixing and ball milling, the particle size distribution range of the porous material will be wider. Therefore, during the coating process, the actual particle size distribution range of the porous material is much larger than the particle size distribution of the prepared porous material. Therefore, the particle size range of the porous material applied in the present invention is 1-1500 nm, preferably 50-1000 nm, and further preferably 100-500 nm.

[0054] Similarly, by Figure 2 As shown in (c), the particle size distribution of the ceramic material alumina is 150-600 nm. After slurrying, the size range of secondary particles / aggregate particles becomes larger, and the size of large particles reaches several microns (e.g. Figure 2 Therefore, the particle size range of the ceramic material of the present invention is 1-5000 nm, preferably 100-1500 nm, and more preferably 150-600 nm.

[0055] Test Example 2 1. Thermal shrinkage resistance test The diaphragms obtained in Examples 1-6 and Comparative Examples 1-3 were cut into 10 cm × 10 cm and placed between two preheated glass plates. They were then placed in a forced air oven and the temperature was set to 130°C and maintained for 1 hour. They were then naturally cooled to room temperature in the oven. The sizes of the diaphragms before and after the treatment were compared and the thermal shrinkage was calculated. Three samples of each type were taken for repeated experiments. The results are shown in Table 1.

[0056] The thermal shrinkage rates of the asymmetric coated diaphragms prepared in Examples 1-6 are all less than 5%, which are much lower than the thermal shrinkage rate of Comparative Example 1 (commercial PE diaphragm), slightly higher than the thermal shrinkage rate of Comparative Example 2 (alumina double-sided coated diaphragm), but significantly lower than the thermal shrinkage rate of Comparative Example 3 (metal organic framework material double-sided coated diaphragm), showing excellent anti-thermal shrinkage performance.

[0057] Table 1. Comparison of thermal shrinkage data of Examples 1-6 and Comparative Examples 1-3

[0058] 2. Diaphragm air permeability test The membrane air permeability test (using PAPT-B01 air permeability tester) was performed on Example 1 and Comparative Examples 1-3, and the results are shown in Table 2. The Gurley value is commonly used in the industry to indicate the air permeability of the membrane. This value indicates the time taken for 100 mL of gas to pass through a membrane of a specific area and thickness under a specific pressure, and is a measure of the air permeability of the membrane. The smaller the Gurley value, the better the membrane permeability, which is more conducive to ion transmission.

[0059] As shown in Table 2, compared with the base membrane (Comparative Example 1), the Gurley values ​​of the coated membranes (Example 1, Comparative Examples 2-3) increase, indicating that the ion channel of the membrane is blocked by the coating material. The Gurley values ​​of Comparative Example 1 (base membrane), Comparative Example 2 (alumina double-sided coated membrane), Example 1 (asymmetric coated membrane), and Comparative Example 3 (porous material double-sided coating) increase in sequence, indicating that the air permeability of the above-mentioned membranes deteriorates in sequence.

[0060] Table 2. Air permeability test results of Example 1 and Comparative Examples 1-3

[0061] As for the coated diaphragm, since the amount of adhesive used in the porous material coating is large, it will block the pores between the particles and the pores of the base membrane, resulting in the Gurley value of the porous material coated diaphragm being higher than the Gurley value of the ceramic material coated diaphragm. However, considering that the porous material itself has a large porosity and specific surface area, it can greatly improve the wettability and adsorption of the diaphragm to the electrolyte, which is beneficial to improving the ion conductivity. In addition, the orderly pore structure of the porous material contributes to the uniform transport of ions and inhibits the formation of dendrites. Although the ceramic material coating has good air permeability, its wettability to the electrolyte is weaker than that of the porous material coating.

[0062] The air permeability of the asymmetric coated diaphragm based on a composite of porous material and ceramic material disclosed in Example 1 is between that of the diaphragm coated with porous material and that of the diaphragm coated with ceramic material, meeting the requirements of the diaphragm; at the same time, the gaps in the ceramic material and the pores of the porous material itself can be used to construct a multi-level ion transmission path to enhance the ion conductivity of the diaphragm.

[0063] 3. Ionic conductivity The separators of Example 1 and Comparative Examples 2-3 were assembled into batteries, and the ion conductivity was tested. Battery Assembly: Positive electrode: stainless steel gasket; Negative electrode: stainless steel gasket; Electrolyte: EC∶DMC∶EMC=1∶1∶1 (V∶V∶V), 1 MLiPF6.

[0064] The test results are shown in Table 3. It can be seen that Example 1 (asymmetric coated membrane) has an ionic conductivity similar to that of Comparative Example 3 (porous material double-sided coated membrane), and both are higher than the ionic conductivity of Comparative Example 2 (alumina double-sided coated membrane). This is attributed to the porous material having a higher liquid absorption rate and better wettability to the electrolyte.

[0065] Table 3. Ionic conductivity of Example 1 and Comparative Examples 2-3

[0066] 4. Thermal conductivity test The thermal conductivity of Example 1 and Comparative Examples 2-3 was tested by transient flat plate heat source method (using instrument: TPS2500S), and the reference standard was ISO22007-2. The test results are shown in Table 4, and it can be seen that the thermal conductivity of Example 1 (asymmetric coated diaphragm) is close to that of Comparative Example 2 (alumina double-sided coated diaphragm), and is much larger than the thermal conductivity of Comparative Example 3 (porous material double-sided coated diaphragm). It can be seen that the asymmetric coated diaphragm based on a composite of porous material and ceramic material provided by the present invention has obvious heat transfer enhancement ability compared with a single porous material coated diaphragm. Combined with the thermal shrinkage data in Table 1, it can be seen that the asymmetric coated diaphragm based on a composite of porous material and ceramic material provided by the present invention has a higher safety in use.

[0067] Table 4. Thermal conductivity of Example 1 and Comparative Examples 2-3

[0068] 5. Electrochemical test Electrochemical tests were performed on Example 1 and Comparative Example 2.

[0069] Battery Assembly: Electrolyte: EC∶DC∶EMC=1∶1∶1 (V∶V∶V), 1M LiPF6; Positive and negative electrode materials: lithium sheets with a diameter of 16 mm.

[0070] like Figure 3 The figure is a cycle test performance diagram of the membrane assembled battery obtained in Example 1 and Comparative Example 2. Among them, the charge and discharge curve of Example 1 is stable, and the cycle time is long, indicating that the performance of the membrane in transporting ions and inhibiting dendrites is better. Figure 3 It can be seen that the battery assembled in Comparative Example 2 (alumina double-sided coated diaphragm) had a polarization voltage that was too high in a very short time, and the battery could not continue to be recycled; while the battery assembled in Example 1 (asymmetric coated diaphragm) showed significantly excellent cycle stability.

[0071] In summary, the asymmetric coated diaphragm based on a composite of porous material and ceramic material provided in Example 1 exhibits comprehensive performance superior to that of a single coated diaphragm of porous material or ceramic material, making up for the shortcomings of a single material coating method. Specifically, compared with the diaphragm coated with ceramic material, Example 1 has higher ionic conductivity and cycle stability; compared with the diaphragm coated with porous material, Example 1 has more excellent resistance to heat shrinkage and higher safety in use. Therefore, the asymmetric coated diaphragm based on a composite of porous material and ceramic material provided in Example 1 has the advantages of both porous material and ceramic material, and has high safety and excellent electrochemical performance.

Claims

1. An asymmetric coated diaphragm based on a composite of a porous material and a ceramic material, comprising a base membrane, characterized in that: One side of the base membrane is provided with a porous material coating, and the other side of the base membrane is provided with a ceramic material coating.

2. The asymmetric coated diaphragm based on a composite of porous material and ceramic material according to claim 1, characterized in that: The thickness of the porous material coating is 1-15 μm; the thickness of the ceramic material coating is 1-15 μm.

3. The asymmetric coated diaphragm based on a composite of porous material and ceramic material according to claim 2, characterized in that: The thickness of the porous material coating is 2-10 μm; the thickness of the ceramic material coating is 2-10 μm.

4. The asymmetric coated diaphragm based on a composite of porous material and ceramic material according to claim 1, characterized in that: The particle size of the porous material is 1-1500 nm; The particle size of the ceramic material is 1-5000 nm.

5. The asymmetric coated diaphragm based on a composite of porous material and ceramic material according to claim 1, characterized in that: The porous material in the porous material coating is selected from one or more of metal organic framework materials, covalent organic framework compound materials, Prussian blue materials and zeolite molecular sieve materials; The ceramic material in the ceramic material coating is selected from one or more of aluminum oxide, boehmite, silicon oxide, zirconium oxide, titanium oxide, calcium oxide, zinc oxide, aluminum nitride, boron nitride, silicon nitride and silicon carbide; The base film is a composite of one or more of polyolefin films, polydimethylsiloxane films, polyester films, polyamide films, polyimide films, glass fiber films and non-woven fabrics.

6. The asymmetric coated diaphragm based on a composite of porous material and ceramic material according to claim 5, characterized in that: The metal element in the metal organic framework material is selected from one or more of zinc, zirconium, iron, manganese, magnesium, aluminum, calcium, lanthanum and cerium; The organic ligand in the metal organic framework material is selected from one or more of terephthalic acid, isophthalic acid, fumaric acid, 2-methylimidazole, trimesic acid and derivatives of the above organic ligands.

7. The asymmetric coated diaphragm based on a composite of porous material and ceramic material according to claim 1, characterized in that: The porous material coating and the ceramic material coating both contain a binder; The binder is selected from one or more of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, styrene-butadiene latex, chitosan, polyvinyl alcohol, polyvinyl ethyl ether, polyacrylic acid, polymethyl methacrylate, and guar gum; The amount of binder added in the porous material coating accounts for 3wt%-70wt% of the total solid mass of the porous material coating, and the amount of binder added in the ceramic material coating accounts for 1wt%-40wt% of the total solid mass of the ceramic material coating.

8. The asymmetric coated diaphragm based on a composite of porous material and ceramic material according to claim 7, characterized in that: The amount of binder added in the porous material coating accounts for 10wt%-40wt% of the total solid mass of the porous material coating, and the amount of binder added in the ceramic material coating accounts for 5wt%-15wt% of the total solid mass of the ceramic material coating.

9. The asymmetric coated diaphragm based on a composite of porous material and ceramic material according to claim 1, characterized in that: It is prepared by any composite method of blade coating, roller coating, spray coating, spin coating, dipping, filter pressing, suction filtration, casting and hot pressing; The solvent used in the composite method is selected from one or more of water, methanol, ethanol, isopropanol, ethyl acetate, N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylformamide and N,N-dimethylacetamide.

10. A secondary battery, characterized in that: The secondary battery is a lithium ion battery or a sodium ion battery; The secondary battery comprises a positive electrode sheet, a negative electrode sheet and a separator, wherein the separator uses the asymmetric coated separator according to any one of claims 1 to 9, and the side of the separator provided with the porous material coating faces the negative electrode sheet or the positive electrode sheet.

Citation Information

Patent Citations

  • Waterborne ceramic coated membrane for lithium ion battery and preparation method thereof

    CN105789539A

  • Lithium ion battery diaphragm with high-temperature-resistant coating, and preparation method of lithium ion battery diaphragm

    CN111509168A

  • Porous material coating ion battery diaphragm and preparation method thereof

    CN116345068A

  • Composite coating diaphragm for ion battery and preparation method of composite coating diaphragm

    CN116435709A

  • Asymmetric composite diaphragm for lithium ion secondary cell and preparation method thereof

    CN102522516A

Cited By

  • Polyethylene-based lithium battery diaphragm and preparation method thereof

    CN121332098A

  • Polyvinyl lithium battery separator and method of making

    CN121332098B